Changes in Indian Foreign Policy in Last Decade: Evolution of India's Foreign Policy: An Analysis of the Last Decade (Journal of Advances and Scholarly Researches in Allied Education, 2019)
From 1947 up to today, this paper offers a study of India's foreign policy. It is split into three separate parts of the past. It would also help to clarify why these initiatives have been followed, India's original direction and the adjustments that have taken place over time. The first portion includes the years from 1947 and 1962, the second segment from 1962 and 1991 and the third section from 1946 and today. These three industries are not random to pick from. The first step of the Indian foreign policy under Indian Prime Minister Jawaharlal Nehru reflected the maximum degree of idealism. The second started in the 1962 Chino-Indian boundary war with the catastrophic loss of India. During that time, the early idealism characterizing the foreign policy of the country and the implementation of an approach to foreign policy that was gradually self-help retained elements of nehruvian rhetorical. The third period started with the end of the Cold War and a more realistic economic strategy, strongly related to realism.